MODERN TRENDS IN THE DEVELOPMENT OF TOURIST AND RECREATIONAL SERVICES IN UZBEKISTAN - Zumrad, Usmanova; Alimova, Munisa (International Journal of Psychosocial Rehabilitation, 2020)
The article examines the factors influencing the formation of tourism and recreational services in Uzbekistan in modern conditions, and examines the trends in the development of tourist and recreational services in the regions for 2011-2018. This approach will provide a functional link between the resource potential of the region and the sustainable development of tourism and recreational services in the region. Effective use of existing tourist and recreational potential will lead to the creation of appropriate recreational infrastructure in the regions, the effective use of existing sanatoriums and health facilities, the construction of new ones and the rapid development of tourist and recreational services. Although there are enough recreational facilities in Uzbekistan, given the growing population and the arrival of foreign nationals for recreation and treatment, it was found that the existing facilities do not meet the needs of all vacationers. The creation of appropriate recreational infrastructure in these regions will make a significant contribution to the restoration of health of the population of our country and will increase the flow of foreign tourists.